2020
DOI: 10.1534/g3.120.401153
|View full text |Cite
|
Sign up to set email alerts
|

Genome-Wide Association Study Reveals Novel Candidate Genes Associated with Productivity and Disease Resistance to Moniliophthora spp. in Cacao (Theobroma cacao L.)

Abstract: Cacao (Theobroma cacao L.), the source of chocolate, is one of the most important commodity products worldwide that helps improve the economic livelihood of farmers. Diseases like frosty pod rot caused by Moniliophthora roreri and witches’ broom caused by Moniliophthora perniciosa limit the cacao productivity, this can be solved by using resistant varieties. In the current study, we sequenced 229 cacao accessions using genotyping-by-sequencing to examine the genetic diversity and population structure employing… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
31
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
2
2

Relationship

0
10

Authors

Journals

citations
Cited by 32 publications
(34 citation statements)
references
References 92 publications
1
31
2
Order By: Relevance
“…The GBS method that uses two restriction enzymes is a highly effective method for reducing genome complexity and generating high-quality SNP markers in several crops, including barley, wheat ( Poland et al, 2012 ), and cacao ( Osorio-Guarin et al, 2020 ), which was also demonstrated in the present study. The GBS method has been used previously for simultaneous SNP discovery and genotyping in finger millet ( Kumar A. et al, 2016 ; Gimode et al, 2016 ; Qi et al, 2018 ; Tiwari et al, 2020 ).…”
Section: Discussionsupporting
confidence: 67%
“…The GBS method that uses two restriction enzymes is a highly effective method for reducing genome complexity and generating high-quality SNP markers in several crops, including barley, wheat ( Poland et al, 2012 ), and cacao ( Osorio-Guarin et al, 2020 ), which was also demonstrated in the present study. The GBS method has been used previously for simultaneous SNP discovery and genotyping in finger millet ( Kumar A. et al, 2016 ; Gimode et al, 2016 ; Qi et al, 2018 ; Tiwari et al, 2020 ).…”
Section: Discussionsupporting
confidence: 67%
“…The cocoa collection conserved in the BGVCOL has 565 accessions characterized at the genomic level. The analysis demonstrated a high genetic diversity among groups, supporting that some genetic groups originated in Colombia, which probably is a center of origin for this crop [78].Moreover, this collection has association studies that support a breeding program [79,80]. In addition, researchers from Agrosavia conducted two expeditions in the upper Amazon and the Pacific, searching for wild cacao relatives.…”
Section: Present and Future Actions For Pgrfa That Resulted In High-p...mentioning
confidence: 60%
“…Da Silva et al [96] identified markers on chromosome 4, which were putatively colocalized with a major gene encoding self-incompatibility. Osorio-Guarín et al [97] detected two genes putatively associated with productivity (number of healthy fruits) and seven encoding Frosty Pod disease resistance. It must be borne in mind that genetic variation of quantitative (polygenic, continuous) traits such as yield and disease resistance are controlled by the combined effects of QTL, epistasis (interactions between QTLs) [14], the environment and interaction between environment and QTL [98].…”
Section: Discussionmentioning
confidence: 99%